Pneumococcal vaccination in elderly care facilities in Japan: A cross-sectional, web-based survey - Youngju Kim; Hironori Taniguchi; Kotoba Okuyama; Junpei Kamimoto; Kenji Kawakami (Human Vaccines & Immunotherapeutics)
This study evaluated pneumococcal vaccination status using evaluable data collected from 445 of 1,313 managing directors of elderly care facilities in Japan through an online survey (September 5, 2022-November 25, 2022; UMIN000048747); comparisons were made with the influenza (2021–2022 vaccination only) and coronavirus disease 2019 (COVID-19) vaccination status. Among facilities who kept pneumococcal vaccination records (n = 42), the mean pneumococcal vaccination rate was 31.1%, with the rate being higher for the influenza (93.1%; n = 234) and COVID-19 (94.3%; n = 285) vaccines. Overall, excluding facilities that answered that the corresponding vaccine status at their sites was unknown, the percentage of facilities with high vaccination rates (80% to 100%) was substantially higher for the influenza (80.5%; 351/436) and COVID-19 (89.6%; 396/442) vaccines than for the pneumococcal vaccine (6.5%; 24/370). Multivariable analysis showed that major factors associated with a high pneumococcal vaccination rate (≥15%) were “managing director’s willingness to recommend” and “pneumococcal vaccination request from the residents.” The most common reason for their willingness to recommend the pneumococcal vaccine was that it is an effective disease prevention strategy (83.3%; 65/78) and for their unwillingness to recommend the pneumococcal vaccine was the inability to understand the effectiveness of the vaccine (43.6%; 17/39). In conclusion, there is a need to improve pneumococcal vaccination rates in elderly care facilities in Japan. Strategies such as increasing awareness and encouraging pneumococcal vaccine recommendation among managing directors, especially for residents not eligible for the national subsidy program, and providing regular training on the pneumococcal vaccine for staff and residents are required.